Nutritional properties and osteogenic activity of enzymatic hydrolysates of proteins from the blue mussel (Mytilus edulis). Issue 12 (6th November 2019) - Xu, Zhe; Zhao, Fujunzhu; Chen, Hui; Xu, Shiqi; Fan, Fengjiao; Shi, Pujie; Tu, Maolin; Wang, Ziye; Du, Ming
Abstract : Seafood provides a range of health benefits due to its nutritional and bioactive components. The proteins and peptides from Mytilus edulis have good bone growth promoting activities. Abstract : Seafood provides a range of health benefits due to its nutritional and bioactive components. However, the bioactive peptides derived from Mytilus edulis proteins were seldom reported, especially their beneficial effects related to bone growth in vitro and in vivo . In this study, the water soluble protein from Mytilus edulis was isolated and the osteogenic activity of Mytilus edulis protein was determined in vivo . The protein from Mytilus edulis was subjected to simulated digestion in vitro, and the hydrolysate of different stages for osteogenic activity by osteoblast proliferation. It was found that the hydrolysate, derived from proteins hydrolyzed by pepsin for 2 h and trypsin for 3 h, showed high osteogenic activity, which induced an increase of 35.56 ± 2.92% in mouse-MC3T3-E1-preosteoblast-cell growth and the alkaline-phosphatase activity was 2.94 ± 0.10 mU, which was an increase of 19.78% compared with that of the control. Moreover, the molecular weight distribution of the peptides and the composition of the free amino acids were determined in order to evaluate the nutritional properties. These findings showed that the water soluble protein from Mytilus edulis could be used in functional food as a bioactive ingredient, which would be beneficial for bone growth and health.